Comparison of different surgical approaches for anterior mediastinal tumor - Mao, Yong (J Thorac Dis, 2020)
BACKGROUND: Different video-assisted thoracoscopic surgery (VATS) approaches may related to heterogeneous clinical outcomes in anterior mediastinal tumor surgery. Herein, we assessed the comparison between the subxiphoid and intercostal approach, and also compare the left versus the right incision in the intercostal approach for anterior mediastinal tumor patients. METHODS: Clinical data of patients receiving thoracoscopic anterior mediastinal tumor resection were retrospectively collected. Patients were divided into two groups according to the approaches: subxiphoid and the intercostal group. The intercostal group was further subdivided into two groups according to different sides: left and right incision group. Intraoperative and postoperative variables were compared between subgroups. RESULTS: A total of 238 patients were consecutively included in this analysis; 198 (83.2%) patients received intercostal procedure and 40 (16.8%) patients received subxiphoid approach. After 1:1 propensity score matching, all baseline characters were well balanced between intercostal and subxiphoid approach, left and right intercostal approach. The visual analogue scale (VAS) pain score was lower in patients underwent subxiphoid approach than intercostal group at first post-operative evaluation in 12–24 h (4.36 vs. 2.23; P=0.03). According to left and right approach, postoperative drainage time (1.9 vs. 1.2 days, P=0.016), postoperative drainage volume (312.1 vs. 193.9 mL, P=0.041) and hospitalization time (5.3 vs. 4.1 days, P=0.043) were significantly increased in the left thoracic approach group compared with the right thoracic approach. CONCLUSIONS: Subxiphoid approach is associated with less pain compared with intercostal approach. The right intercostal thoracic approach may offer better clinical effect of short-term postoperative recovery.